2010
DOI: 10.1007/s00228-010-0830-5
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of natural mistletoe lectins after subcutaneous injection

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…administration have shown that molecules applied i.v. were eliminated up to three times faster than when applied s.c [4547]. This finding might also help to explain the much higher frequency of pyrexia observed in s.c. patients compared to i.v.…”
Section: Discussionmentioning
confidence: 82%
“…administration have shown that molecules applied i.v. were eliminated up to three times faster than when applied s.c [4547]. This finding might also help to explain the much higher frequency of pyrexia observed in s.c. patients compared to i.v.…”
Section: Discussionmentioning
confidence: 82%
“…Unfortunately, there is literature lacking showing the pharmacokinetics of mistletoe extracts in mice or humans, but Huber et al . showed for subcutaneous injections in humans, that serum mistletoe lectin levels are highly variable after injection [61]. Furthermore, Frantz et al .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, except the lower frequency of diarrhea, no specific improvement during mistletoe treatment occurred (Table 2). Possible mechanisms how mistletoe treatment could improve the global health status include immunological effects and elevating body temperature [27], because immunological disturbances and an altered circadian rhythm are factors that may contribute to reduced QoL in cancer patients [28]. …”
Section: Discussionmentioning
confidence: 99%